A Comparative Critical Discourse Analysis of U.S. and Pakistani Newspapers’ Coverage on Gender Equality in Pakistan - Habiba Bahjat, (Dialogue Social Science Review (DSSR), 2025)
This study critically compares how Pakistani and U.S. English-language newspapers represent gender equality across five WEF-based dimensions and examine how their discourses challenge or reinforce power structures. Pakistan ranks last among 148 countries in the 2025 WEF Global Gender Gap Report, indicating worsening gender parity. Pakistani media often marginalizes women’s successes and frames them as victims, while U.S. media projects Pakistani gender issues through Western liberal lenses. Using systematic random sampling, the study analyzes opinion pieces, features, and magazine articles from Dawn, The News International, The New York Times, and USA Today (2022–2024), guided by Fairclough’s three-dimensional model and Teun A. van Dijk’s socio-cognitive discourse theory. Results show Dawn uses reformist, symbolic narratives and The News relies on crisis-driven frames. Both avoid deep structural critique. U.S. media emphasizes external aid. Pakistani outlets should adopt rights-based, accountability-focused narratives; U.S. media must report with nuanced, decolonial frames; future research should examine transgender representation and include vernacular platforms. Keywords: Critical Discourse Analysis, Pakistani, Newspapers, Gender Equality